Collaborative Leadership and Curriculum Reform: A Phenomenological Inquiry into Indonesia’s Kurikulum Merdeka - AD, Nahira; Baderiah, Baderiah; Ilham, Dodi (International Journal of Asian Education, 2025)
Curriculum reform in Indonesia through the Kurikulum Merdeka aims to create more flexible, contextual, and student-centered learning. However, the implementation process at the school level remains challenging, especially in non-pilot institutions with limited resources. This study explored how the Kurikulum Merdeka was implemented at SMP Negeri 1 Nuha, focusing on four key dimensions: curriculum planning, coordination, instructional practices, and evaluation. Using a qualitative phenomenological design, data were collected through interviews, classroom observations, and document analysis involving 12 participants consisting of the principal, teachers, administrative staff, and students. The findings reveal that curriculum planning was conducted collaboratively but remained adaptive rather than innovative, as teachers still relied on government templates. Coordination and collaboration were supported by strong principal leadership and professional learning communities, though participation levels varied across departments. Instructional implementation demonstrated a gradual shift toward project-based and differentiated learning, despite limited facilities and uneven teacher readiness. Evaluation practices emphasized holistic assessment, integrating academic, character, and social aspects aligned with the Profil Pelajar Pancasila. Overall, the study concludes that successful curriculum implementation depends not only on policy clarity but also on local school ecosystems that nurture teacher collaboration, leadership, and continuous learning. The findings suggest that ongoing professional development, reflective practice, and adequate institutional support are critical to realizing the goals of the Kurikulum Merdeka in diverse educational contexts.